Association between single-nucleotide polymorphisms of ADAMTS13 and severe COVID-19: a case-control study in Chinese Han adults - Daoyan Tang; Xiaoshu Liu; Jianqing He (Archives of Medical Science)
Introduction Material and methods Results Conclusions